THE RELATIONSHIP BETWEEN KNOWLEDGE OF ICU CARE AND THE LEVEL OF FAMILY ANXIETY IN THE ICU ROOM OF RSI PATI - Dwi Agustini; Feri Catur Yuliani; Dwi Puji Susanti; Akbar Amin Abdullah (RADJA PUBLIKA, 2025)
The Intensive Care Unit (ICU) is a hospital service that handles critically ill patients, caring for those at high risk of developing an emergency. This is what creates a sense of security for the patient's family. The aim of this study was to determine the relationship between knowledge of ICU care and the level of anxiety of families undergoing care in the ICU. This study is a quantitative descriptive correlation study. The sample size was 21 respondents using total sampling and analyzed using sperm rink. The results of the study between the level of knowledge of ICU care and the level of family anxiety in the ICU room of RSI Pati obtained p (sig) = 0.000. Conclusion: This study found a correlation between knowledge of ICU care and the level of family anxiety.